Traduttore, traditore: The expert work of producing global (yet local) market classifications - Claudio E. Benzecry (economic sociology. perspectives and conversations, 2022)
In my new book, The Perfect Fit. Creative Work in the Global Shoe Industry (Benzecry 2022), I study the work of repair and maintenance necessary to keep the global scale going. I do so by studying the work and lives of experts in charge of design and development of shoes for the US market. Research for this project began in 2012; I conducted five years of research in between New York City (USA), Dongguan (China), and Novo Hamburgo (Brazil), scrutinizing the friction (Tsing 2005) between expert work and cheap labor in the production of a ubiquitous commodity: shoes.
Keywords: 300